German expressionist theatre - Kuhns, David F. (Cambridge Univ. Press, 1997)
German Expressionist theatre: the actor and the stage considers the powerfully stylized and anti-realistic styles of symbolic acting on the German Expressionist stage from 1916 to 1921. It relates this striking departure from the dominant European acting tradition of realism to the specific cultural crises that enveloped the German nation during the course of its involvement in World War I. Unlike any of the very few publications in English on stage Expressionism, this book describes three distinct Expressionist acting styles, all of which in their own ways attempted to show how symbolic stage performance could be a powerful rhetorical resource for a culture struggling to come to terms with the crises of historical change. The examination of previously untranslated portions of Expressionist scripts and actor memoirs allows for an unprecedented focus on description and analysis of the acting itself.
Keywords: Acteren; Art dramatique; Expressionisme; Expressionnisme dans la littérature; Théâtre - Allemagne - Histoire - 20e siècle; Théâtre allemand - 20e siècle - Histoire et critique; Théâtre expérimental - Allemagne - Histoire - 20e siècle; Geschichte; Acting; Experimental theater; Expressionism in literature; German drama; Theater; Expressionismus